Controle estatístico do processo de tratamento de efluentes domésticos em ETE com linhas de tratamento anaeróbio e aeróbio - Oga, Leticia de Carvalho (2020)
Among other factors, access to the ecologically balanced environment depends on basic sanitation. Therefore, the correct disposal of wastewater in the environment reduces the negative impacts on the use of water supply, which are already overloaded due to availability, economic-social and political influence. Domestic sewage treatment must meet regulations and parameters to ensure the least possible interference in the receiving system of treated effluents. However, several factors interfere in the characteristics of the wastewater, which often impairs the quality of the treatment process. Therefore, it is essential to monitor the adequacy of the treatment efficiency, identifying the possible causes of interference in order to minimize or mitigate them. Among the ways to attest quality or the adequacy of the process is through statistical process control (SPC) tools. The present work aimed to apply the control graphing tools and process capacity indexes in a domestic wastewater treatment plant (WWTP) in order to verify the performance of different treatment lines of the WWTP, in terms of suitability of the installed treatment and the quality of the receiving water body. pH, COD and settleable solids data were observed in the anaerobic, aerobic and final mixture treatment lines. The period analyzed was from January 2016 to December 2018. The control chart applied was Shewhart´s chart and the capability index Cp, Cpl, Cpu, Cpk, Cpm and Cpmk. Shewhart's chart showed that all parameters in all lines are not under statistical control, but that the aerobic treatment line assisted in improving the control of the COD parameter in the mixing line. Despite presenting great variability in the process, the process capacity indexes show that the WWTP is able to meet the specifications and meet the release standards required by environmental legislation, with the exception of settleable solids for the anaerobic and mixing lines.